Merging perspectives: obstacles to recovery for youth from refugee backgrounds with comorbidity. (June 2015) - Posselt, Miriam; Procter, Nicholas; de Crespigny, Charlotte; Galletly, Cherrie
Objective: This research aimed to identify challenges encountered by young people from refugee backgrounds with co-existing mental health (MH) and alcohol and other drug (AOD) problems (comorbidity) and sought to compare the perspectives of refugee youth and service providers in a metropolitan region of Adelaide, South Australia. Methods: Semi-structured interviews were conducted with two groups of participants: young people from refugee backgrounds (African, Afghan, Bhutanese) and workers from MH, AOD and refugee support services. Results: The refugee youth reported that the biggest difficulty they face once they develop MH and AOD problems is social disconnectedness. They lacked awareness that services are available to support them. In contrast, clinicians rated difficulty accessing and receiving culturally competent comorbidity care as the greatest challenge. Other reported challenges were relatively consistent across both groups. Conclusions: This study has implications for how we engage these young people in services, prioritise areas of care and effectively treat and support refugee youth experiencing comorbidity. These findings emphasise the need for a combined therapeutic casework approach, addressing needs such as social connectedness, housing, education and employment.